The Development of Philosophical Interpretation in The Islamic Intellectual Tradition: From the Golden Age to the Emergence of Islamic Interpretation - Jauharah Khairun Nisa; Muh Asriadi AM (UIN Sunan Gunung Djati Bandung, 2026)
This study discusses the development and characteristics of philosophical interpretation in the Islamic intellectual tradition by tracing its historical dynamics from the golden age of Islam to the emergence of ishari interpretation. The research approach used is qualitative with a descriptive-analytical method based on a literature review of classical and contemporary literature. The results of the study show that philosophical interpretation emerged as a response to the interaction between rational-philosophical thought and religious understanding in the context of medieval Islamic intellectualism. During the Abbasid period, the integration of Greek philosophy with Islamic thought gave birth to a style of rational interpretation represented by figures such as Al-Farabi, Ibn Sina, and Ibnu Rusyd. However, this study also found that the emergence of ishari interpretation became a spiritual transition from philosophical rationality to a Sufi intuitive approach in understanding the text of the Qur'an. Theoretically, this research contributes to mapping the evolution of the epistemology of interpretation, while practically it can be an academic reference for studies of interpretation based on philosophy and Islamic spirituality.